Immigrant Youth Program: A Model for Educational and Personal Success. Issue 2 (4th March 2022) - Garcia, Martha Lucia; Carnes, Stephanie; Hanssen, Daria
Abstract: Central American youth constitute one of the largest groups of newcomers in U.S. public schools, particularly in urban areas. Many have experienced traumatic events and interrupted or limited formal education. These factors, coupled with cultural and language differences, may lead these youth to struggle in public schools, unless specifically tailored programming is provided. The loss of family, and what is familiar to them, may lead them to feel alone. This article presents a model that meets the unique academic and mental health needs of Central American immigrant youth by harnessing the power of community in a school setting. The study findings indicate that a model premised on relational safety, cultural acceptance, and educational support enhances students' motivation and commitment to their academic and professional goals. Further, creating an environment that prioritizes a sense of belonging can foster a sense of well-being. School social workers are critical to the implementation of such a model, which requires a nuanced understanding of cultural context, sociopolitical factors that surround public policy, lived experience, impact of trauma, and the recognition of the innate strength of these youth. The article presents a way for navigating the challenges, while maximizing the power of community and belonging in these children's lives.